Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Konsumen Hotel Shangri-La Surabaya - Sarmento, Milenia Hanna Lopes; Aribowo, Handy (Peneliti.net, 2024)
This study aims to investigate the influence of service quality and price on customer loyalty at Shangri-La Hotel Surabaya. The research method used was quantitative research. The study found that the high service quality of Hotel Shangri-La Hotel Surabaya has a significant positive effect on customer loyalty, while reasonable pricing also contributes to increasing customer loyalty. Good service quality encourages customers to build a strong relationship with the company, enables the company to understand customer expectations and needs, and enhances positive customer experiences. Additionally, pricing that is in line with standards can meet customer expectations and contribute to their satisfaction, which, in turn, increases customer loyalty. These findings highlight the importance of hotel management in improving service quality and setting competitive prices to achieve high customer loyalty and maintain a strong market share in the hospitality industry.